A invisibilidade epistemológica de conhecimentos não convencionais e sua apropriação pelo direito na ótica dos direitos fundamentais: uma análise à partir das cartas psicografadas e a racionalidade jurídica brasileira - Costa, Lucas Kaiser (2015)
Western modernity was founded on the pillars of scientific knowledge and the modern state law, so that while the first sought to inform the criteria of truth and falsehood for explanations about life, the second established the form of organization of modern states and social regulation. It was up to modern science the primacy of truth and the epistemological role as the only form of credible knowledge, so all knowledge that does not base itself on scientific methods and its precepts was rejected or made invisible, as if it were even existing, and the Law, influenced by the scientistic positivism, followed the same path, that is, to be valid should be emanated by the very modern state, otherwise it would be relegated to the invalidity, illegality, or characterized as "non-law". Rationality forged from modernity, then, based on these two pillars and totaling as only possible reality, was highly exclusionary invisibilizando forms of unconventional know that not reproduce itself. In this sense, the present study, based on the methodology of the "sociology of absences", Boaventura de Sousa Santos, seeks to verify whether the maintenance of the epistemological invisibility that hangs over the unconventional knowledge, from its failure to incorporate the Law, has the power to mitigate fundamental rights. For this, the work was divided into four chapters are concerned with: present the methodological application used in research; analyze the paradigm of modernity, its crisis and its epistemological aspects, and the signs of the emerging paradigm; discuss the role of fundamental rights in the new paradigm, and the need to build a legal pluralism; and examine the appropriation of non-conventional knowledge by Law from a specific object, the psychographic letters, for in the end, to demonstrate the demand for a complex paradigm, able to recognize and materialize human rights now reinterpreted from the pluralization of dogmatic law, without which one can not promote the deconstruction of modern epistemological invisibility, which will result in the mitigation of the fundamental rights of individuals marginalized by instrumental modus of modern Western rationality.